Performance analysis for randomly distributed mixed carbon nanotube bundle interconnects. (1st November 2014) - Majumder, Manoj Kumar; Kumar, Jainender; Kumar, Vobulapuram Ramesh; Kaushik, Brajesh Kumar
Abstract : During the recent past, carbon nanotubes (CNTs) have rapidly gained importance in an intensely growing researched area of interconnects. For various reasons, bundled CNTs are often preferred over single‐walled CNTs (SWCNTs) or multi‐walled CNTs (MWCNTs). However, during fabrication, it is difficult to control the growth of a densely packed bundle having SWCNTs with uniform diameters or MWCNTs with an identical number of shells. Therefore, a realistic CNT bundle is in fact a mixed CNT bundle (MCB) that consists of SWCNTs and MWCNTs. In light of these facts, an analytical model of a MCB that follows the random distribution of CNTs in a bundle is introduced. Depending on the probability of distribution of CNTs having different diameters, a compact multi‐conductor transmission line (MTL) and a simplified equivalent single conductor (ESC) model are presented. Encouragingly, the simplified ESC model exhibits an average error of only 2.44% at different interconnect lengths compared with the delay obtained through the MTL approach. Mean diameter and tube density of the MCB are mapped to the ESC model to analyse the propagation delay, power dissipation and crosstalk. Irrespective of interconnect lengths, it is observed that the performances are significantly improved for higher tube density in a MCB.